Former Yugoslav Republic of Macedonia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in the Former Yugoslav Republic of Macedonia during 1990-95. The financial stabilization in 1994 was a result of three key policy changes. The National Bank abolished its system of passively rediscounting selective commercial bank credits and the emphasis of monetary policy was switched to inflation control. A broad range of fiscal measures ensured a decline in the public sector deficit from 11 percentage points of gross social product in 1993 to 3 percentage points in 1994. There was a 50 percent drop in measured industrial production between 1990 and 1994.